2019
DOI: 10.1111/jerd.12523
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of repairs on bis‐acryl resin submitted to thermal aging and immersion in beverages

Abstract: Objective Defects/bubbles can occur during the manufacture of bis‐acryl resin provisional restorations, requiring repair or new prosthesis. This study evaluated the color stability of bis‐acryl resin specimens repaired, aging, and immersioned in beverages. Material and methods Eighty disks were made of bis‐acryl resin. Twenty disks were not repaired (BCR), 20 disks were repaired with the same bis‐acryl resin (BCR‐BCR), 20 disks were repaired with flowable resin (BCR‐FR), and 20 disks received an adhesive layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Regarding bis-acryl resins, studies that evaluated their behavior in staining solutions concluded that pigments may be able to penetrate the material through the gaps formed after the setting reaction, since bis-acryl resins have a more heterogeneous composition, which facilitates staining and consequent absorption of pigments [19][20][21]. However, there are few studies that assess the color stability of this group of resins, including aging by cigarette smoke.…”
Section: Rocha Rs Et Almentioning
confidence: 99%
“…Regarding bis-acryl resins, studies that evaluated their behavior in staining solutions concluded that pigments may be able to penetrate the material through the gaps formed after the setting reaction, since bis-acryl resins have a more heterogeneous composition, which facilitates staining and consequent absorption of pigments [19][20][21]. However, there are few studies that assess the color stability of this group of resins, including aging by cigarette smoke.…”
Section: Rocha Rs Et Almentioning
confidence: 99%
“…In addition, a correlation has been reported between the residual double bonds and internal color change of light-cure composite resins 10 . The possible causes include oxidation of unreacted double bonds, and chemical degradation and formation of colored degradation products 10,12 .…”
Section: Introductionmentioning
confidence: 99%